Myths and mistakes in New Testament textual criticism - Hixson, Elijah; Gurry, Peter J.; Wallace, Daniel B. (InterVarsity Press, 2019)
A renewed interest in textual criticism has created an unfortunate proliferation of myths, mistakes, and misinformation about this technical area of biblical studies. Elijah Hixson and Peter Gurry, along with a team of New Testament textual critics, offer up-to-date, accurate information on the history and current state of the New Testament text that will serve apologists and offer a self-corrective to evangelical excesses.